Slaves from the North Finns and Karelians in the East European slave trade, 900-1600 - Korpela, Jukka 1957- (Studies in global slavery, 2019)
In this book Jukka Korpela offers an analysis of the trade in kidnapped Finns and Karelians into slavery in Eastern Europe. Blond slaves from the north of Europe were rare luxury items in Black Sea and Caspian markets, and the high prices they commanded stimulated and sustained a long-distance trade based on kidnapping in special robbery missions and war expeditions. Captives were sold into the Volga slave trade and transported through market webs further south. This business differed and was separate from the large-scale raids carried out on Crimeans for enslavement in Eastern Europe, or the mass kidnappings characteristic of Mediterranean slavery. The trade in Finns and Karelians provides new perspectives on the formation of the Russian state as well as the economic networks of official and unofficial markets in Eastern Europe.